2003
DOI: 10.1191/0269216303pm754oa
|View full text |Cite
|
Sign up to set email alerts
|

Burden of care in amyotrophic lateral sclerosis

Abstract: The low burden of ALS carers may be caused by the low incidence of problem behaviour in ALS patients. However, if problem behaviour exists, carers participate more often in support groups, indicating the need for assistance. The burden of care increases with the functional impairment. Support for the carers has to start sooner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
2
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 20 publications
2
75
2
3
Order By: Relevance
“…There are indications that female MND caregivers may experience greater burden than men (13,31,32,53,59).…”
Section: Mitigating Factors Associated With Caregiver Burden and Qualmentioning
confidence: 99%
See 2 more Smart Citations
“…There are indications that female MND caregivers may experience greater burden than men (13,31,32,53,59).…”
Section: Mitigating Factors Associated With Caregiver Burden and Qualmentioning
confidence: 99%
“…In about 15% of cases, people with MND will develop frontotemporal dementia which presents additional challenging neurobehavioral symptoms for family caregivers including irritability, impulsivity, loss of insight, self-centeredness and lack of empathy, aggression, food cravings, and obsessions and/or compulsive behaviors (30). A German study found burden is markedly higher in MND caregivers who report encountering "problem-behavior" (32). Cognitive changes have a profound impact on caregivers, sharply increasing depression and burden and negatively impacting their quality of life (31).…”
Section: Cognitive and Neurobehavioral Declinementioning
confidence: 99%
See 1 more Smart Citation
“…Here, we report on two studies examining temporal cognitive changes in ALS. Indentifying and acknowledging that ALS patients may also be dealing with cognitive and/or behavioral changes in addition to their debilitating motor declines may help their physicians and caregivers to better care for the individual with ALS and anticipate problems that they may experience throughout the disease progression (Hecht et al, 2003). These cognitive changes can affect the everyday social interactions of ALS patients, and they are vital for the execution of more complex tasks such as decision-making, problem solving, and management of occupational demands (e.g., multi-tasking).…”
mentioning
confidence: 99%
“…In another study, 1 we found that time allocation affected the perceived quality of life and perceived burden of ALS caregivers, which was mostly related to "personal and social restrictions" 7 or to "time-dependence burden" and "developmental burden" (which is interpreted as the feeling of the person to be out of time with respect to his or her peers).…”
mentioning
confidence: 99%